IFPRI Climate Change - International Food Policy Research Institute (2014)
The IFPRI Climate Change website includes blogs, research outputs and project updates from the research and work on climate change at the International Food Policy Research Institute (IFPRI). IFPRI researchers and their many partners and collaborators seek to assist small-scale farmers to find ways to sustainably adapt to and build resilience toward a changing climate. The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) funds much of the climate-related work at IFPRI, which spans the globe from Latin America, Africa, to South and South East Asia.